Evaluating the influence of financial control mechanisms on the financial performance of Malaysian Cooperatives - Abd Razak, Nor Alyani; Mat Jusoh, Yusri Huzaimi; Hassan, Raabatul Azira; Ishak, Rosbi; Abd Rahman, Samsuria; Muhamad, Azim Izzudin (International Journal of Accounting, Finance and Business, 2024)
Malaysian cooperatives are an effective economic engine in helping the community, especially the B40 and M40 group, most affected by the unstable economic problems due to the Covid-19 pandemic. Hence, the government needs to ensure that the cooperative sector can improve its performance, particularly in financial aspects, to serve its members. This research is conducted to determine the improvement measures related to financial control mechanisms that need to be emphasized at the level of regulators, cooperatives and stakeholders to reduce the risk of loss and achieve the financial objectives set by the government. The research examines the relationship between financial control mechanisms: financial reporting, budgetary control, risk management, and cooperative financial performance. This study employed a quantitative approach and purposive sampling, with respondents selected based on predetermined criteria requiring them to utilize their experience and knowledge as cooperative board members to respond to the questionnaire. There were 122 returned surveys, of which only 119 were usable for analysis. The result showed that financial control mechanisms are positively related to financial performance as all three components of financial control mechanisms used in cooperatives, consisting of financial reporting, budgetary control and risk management, have a positive relationship with financial performance. The findings from this study generally aimed to provide helpful information for cooperatives’ stakeholders, in determining the right approach to increase cooperatives’ financial performance.